Sound: Dialogue, Music, and Effects - Hannah M. Chambers (Journal of Applied Communications, 2022)
Book review of Sound: Dialogue, Music, and Effects, edited by Kathryn Kalinak.
Keywords: Video; Sound; Music; Textbook; Supplemental Resource